Chain of gold - Clare, Cassandra (Clare, Cassandra. Last hours., 2020)
Cordelia Carstairs, a Shadowhunter trained to battle demons, travels with her brother to London where they reconnect with childhood friends but soon must face devastating demon attacks in the quarantined city.